Static and dynamic study of composite beams with a new interlaminar sliding field using different beam theories - Mohamed Krachaï, Rachida; Elmeiche, Noureddine; Mechab, Ismail; Bernard, Fabrice; Abbad, Hichem (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: The present work aims to carry out a static and dynamic investigation of composite beams composed of two elements connected together, with a partial interaction between the beam layers, while taking into account the interlaminar sliding effect.Methods: A new interlaminar slip field which takes into account, for each layer, the axial displacement, the rotation due to bending, and the high-order transverse shear with a new warping shape function, has been introduced in this study. The equilibrium equations were solved analytically based on the principle of Hamilton. In addition, the numerical resolution of these equations was based on the principle of minimizing all energies using the Ritz method, while taking into account different beam theories. Afterwards, a comparative study was carried out in order to calculate the natural vibration frequencies of two composite beams made of steel and wood materials. Results: It was found that the results obtained for the ten natural vibration frequencies are in perfect agreement with those reported in previous works found in the literature.Conclusion: Further, a detailed study was conducted, depending on the geometric and material parameters, for the two mixed materials, i.e., concrete-wood and steel-concrete, with two interlaminar sliding fields, namely the classical sliding field based on the Timoshenko beam theory and a new interlaminar sliding field that is based on the high order theory. Furthermore, bending was studied in the static case in order to examine the effect of the interlaminar shear force on short and long beams.
Keywords: static and dynamic study; composite beams; partial interaction; new interlaminar slip field; high order transverse shear; new warping shape function; Ritz method